2016
DOI: 10.1104/pp.16.00923
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Failure of Fine Root Cortical Cells Initiates Plant Hydraulic Decline during Drought

Abstract: Root systems perform the crucial task of absorbing water from the soil to meet the demands of a transpiring canopy. Roots are thought to operate like electrical fuses, which break when carrying an excessive load under conditions of drought stress. Yet the exact site and sequence of this dysfunction in roots remain elusive. Using in vivo x-ray computed microtomography, we found that drought-induced mechanical failure (i.e. lacunae formation) in fine root cortical cells is the initial and primary driver of reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
122
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 66 publications
(88 reference statements)
11
122
1
Order By: Relevance
“…According to the segmentation hypothesis, plants sacrifice organs of lesser importance and investment to save organs that are critical for longterm survival and propagation (Zimmermann, 1983). Such segmentation is supported in grapevine by the finding that petioles and roots are more vulnerable to cavitation than stems (Lovisolo et al, 2008;Charrier et al, 2016;Cuneo et al, 2016;Hochberg et al, 2016a). Combining these previous findings with our observation that, on average, the midrib cavitates before higher vein orders (for clear visualization, see Supplemental Fig.…”
Section: Discussionsupporting
confidence: 80%
“…According to the segmentation hypothesis, plants sacrifice organs of lesser importance and investment to save organs that are critical for longterm survival and propagation (Zimmermann, 1983). Such segmentation is supported in grapevine by the finding that petioles and roots are more vulnerable to cavitation than stems (Lovisolo et al, 2008;Charrier et al, 2016;Cuneo et al, 2016;Hochberg et al, 2016a). Combining these previous findings with our observation that, on average, the midrib cavitates before higher vein orders (for clear visualization, see Supplemental Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Our finding is consistent with recent studies on potted individuals showing an association between the onset of optically observed xylem embolism and loss of hydraulic function in leaves across several plant functional types (Brodribb et al ., ; Hochberg et al ., ; Skelton et al ., ). Although hydraulic impairment at low leaf water potential has consistently been shown to be caused by embolism (Brodribb et al ., ; Hochberg et al ., ; Skelton et al ., ), other mechanisms may also reduce k leaf (Cuneo et al ., ; Scoffoni et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, rather than experience this PLC in the branches or roots, the large loss of conductivity in this study appeared to occur below ground in locations or tissues other than coarse roots. Possible explanations for how this belowground hydraulic conductance would decline in situ are either declines in soil hydraulic conductivity, mechanical failure (i.e., roots no longer in contact with soil particles), hydraulic failure of fine root cortical cells or fine root embolism upon exposure to drying soil (Cuneo, Knipfer, Brodersen, & McElrone, ).…”
Section: Discussionmentioning
confidence: 99%